The Relationship between Parents' Emotional Support and Students' Learning Independence in MDTA Surau Gudang Kota Solok - Fitriani, Nadya; Sunarti, Vevi (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This research is motivated by the low self-reliance of students in MDTA Surau Gudang Kota Solok. This is allegedly due to the emotional support of parents. This study aims to (1) Describe emotional support of parents (2) Describe the learning independence of students and (3) See the relationship of emotional support of parents with learning independence in MDTA Surau Gudang Kota Solok. The type research is a study with a quantitative approach to the type of correlation. The study population were students in MDTA Surau Gudang Kota Solok from class I, II, III, and IV, amounting to collection techniques using stratified random sampling techmique using questionnaires. Data analysis techmique using the percentage product moment formula. The results showed that (1) the emotional support of parents is low (2) the learning independence of students in MDTA Surau Gudang Kota Solok is still low (3) there is a significant relationship between the emotional support of parents and the learning independance of students in MDTA Surau Gudang Kota Solok. Its is recommended to (1) parents should further enhance their emotional support to optimize students’learning (2) for teacher should be able to provide motivation and also creative in using learning media so as to bring up the spirit of learning that makes students have the independence of learning (3) it is expected to other researchers to choose other variables related to learning independence.